Thermal performance correlation of horizontal closed-loop oscillating heat pipes - Piyanun Charoensawan (2018)
The thermal performance of a closed-loop oscillating heat pipe which operates at horizontal orientation (Horizontal closed-loop oscillating heat pipe, HCLOHP) was dimensionally analyzed to formulate the empirical correlation. The various dimensionless groups which were supposed to influence the thermal performance of a HCLOHP was considered coupling with the quantitative results of the heat transfer characteristics of HCLOHP. These available results carried out in our previous work were covered a wide range of parameter variations and the investigated parameters consisted of tube inner diameter, working fluid, effective length of fluid flow path between the evaporator and condenser sections, number of turns, filling ratio and evaporator temperature. The influence dimensionless groups were found as Prandtl number of liquid (Pr 1), Karman number (Ka), modified Jacob number (Ja*) with adding the influence of filling ratio, Bond number (Bo), Kutateladze number (Ku) and kc/ka (the ratio of the thermal conductivities of the cooling fluid at the required temperature and the ambient air at 25°C used as a coolant of condenser part in our previous experiment). The thermal performance correlation of a HCLOHP was successfully developed in the nondimensional form of power function by using the curve fitting with 98 reliable data sets and the system of equations was solved by the Gauss elimination method. The standard deviation (STD) of this empirical model is ±30%. Moreover this correlation absolutely agrees with 13 sets of reliable data of HCLOHP with using water, R123 and ethanol as working fluid in another our previous research. From the attained nondimensional correlation it can be concluded that Ku or dimensionless group representing the thermal performance of HCLOHP improves with increasing Pr1, Ka and k c/ka and with decreasing Ja* and Bo. © 2007 IEEE.